Recurrence of Infantile Hemangiomas Treated with Propranolol - Bagazgoitia, Lorea; Hernández-Martín, Ángela; Torrelo, Antonio (Pediatric dermatology, 2011)
:  Propranolol has shown to be effective in the treatment of infantile hemangiomas (IH), but several cases of recurrences have been reported so far. We describe five cases of IH recurrence after propranolol treatment was stopped in 26 patients treated with propranolol all of whom were observed for at least 9 months after treatment was discontinued. Recurrence was present in 5 of 26 cases, yielding a recurrence rate of 19%. All cases were in females. Time from withdrawal to recurrence ranged from 0 to 6 months. In four of five cases, the lesion relapsed after the age of 11 months. Four of the five cases presented partial recurrences, whereas in one case, recurrence was complete. In the majority of cases, recurrence appeared in the deep component of the IH. Early treatment withdrawal or a long proliferative phase of IH are potential causes of hemangioma recurrence, although the exact mechanism remains unclear. The vascular endothelial growth factor receptor might be involved, as well as incomplete apoptosis during treatment.